BUFFER CAPACITY OF SURFACE WATERS AS A GEOCHEMICAL FACTOR OF THEIR RESISTANCE TO ACIDIFICATION - Lozovik P.A.; Potapova I.Yu.; Bantsevich T.V. (My University, 2007)
The acidification of natural waters is a serious environmental problem. The causes of water acidification can be anthropogenic factors and natural geological processes, but the main factor intensifying the process of acidification is anthropogenic acidic contamination. The resistibility of natural water bodies to acidification is assayed using the criterion of acid neutralizing capacity (ANC) and buffer capacity (β).